Zakaz propagowania komunizmu lub innego ustroju totalitarnego przez pomniki na podstawie tzw. ustawy dekomunizacyjnej w świetle orzecznictwa sądów administracyjnych - Bojarski, Adam (Studia Prawa Publicznego, 2025)
One of the objectives of the Decommunization Act is to remove monuments or other objects from public space that propagate communism or another totalitarian system. A significant problem is posed by the scale of this undertaking, which is difficult to estimate. Consequently, in some cases the opinion of the IPN was disagreed with and challenged in the administrative courts. The administrative courts were required to assess whether a given monument or object defined under the Decommunization Act could propagate communism or another totalitarian system. From the case law of the administrative courts it is possible to deduce several principles which guided these courts in assessing whether a given monument or object may propagate communism or another totalitarian system. In the Polish public space there are only monuments associated with the ‘activities’ of the Red Army and not with other totalitarian systems such as fascism or Nazism, hence the name ‘decommunization of monuments’. Despite the small body of case law, it must be stated that the so-called ‘decommunization of monuments’ is not a simple issue. The purpose of this article is to present the body of final judgments of the Provincial Administrative Courts and the Supreme Administrative Court concerning the ‘decommunization of monuments’. Unfortunately, the Decommunization Act has not dispelled doubts in this respect, which is why, in the author’s opinion, an analysis of the case law of administrative courts is a valuable supplement to this Act. Despite the introduction of the Decommunization Act, we can still find monuments in public space related to the ‘activities’ of the Red Army, although there are fewer and fewer of them with the passing of time.